2003
DOI: 10.4049/jimmunol.170.10.5152
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of IL-4 Receptor Signaling and IL-10 to Susceptibility toLeishmania major

Abstract: The roles of IL-10 and IL-4 receptor signaling were evaluated in a murine model of Leishmania major infection. In previous studies the L. major substrain LV39 caused progressive, nonhealing lesions in BALB/c mice deficient for IL-4R α-chain (IL-4Rα), while substrain IR173 was highly controlled. To explore whether IL-10 is responsible for inducing susceptibility to LV39, wild-type and IL-4Rα−/− mice were treated with anti-IL-10R mAb, and in a genetic approach, the IL-4Rα−/− mice were crossed with BALB/c IL-10−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
101
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 33 publications
14
101
1
1
Order By: Relevance
“…Our results from post vaccination and pre challenging are desirable and as it was demonstrated in the present experiment, the best vaccinated group was LT group and the best injection dose was 100 µg/0.1 ml nominated LT100 which had lowest spleen white pulp expansion and highest levels of IL-17 and IL-23. These finding confirmed our previous results concerning expansion of spleen white pulp [35] and the levels of serum IL17 and IL-23 in the vaccinated animals [36][37][38][39][40]41]. This is a satisfactory results for this new leishmania Vaccine, since IL-23 and IL-17 axis and activation of JAK-STAT is essential for immunity against Chronic Mucocutaneous Candidiasis (CMCC) and CMCC also is Mendelian disease that leishmaniasis is one of its Complications.…”
Section: Discussionsupporting
confidence: 79%
“…Our results from post vaccination and pre challenging are desirable and as it was demonstrated in the present experiment, the best vaccinated group was LT group and the best injection dose was 100 µg/0.1 ml nominated LT100 which had lowest spleen white pulp expansion and highest levels of IL-17 and IL-23. These finding confirmed our previous results concerning expansion of spleen white pulp [35] and the levels of serum IL17 and IL-23 in the vaccinated animals [36][37][38][39][40]41]. This is a satisfactory results for this new leishmania Vaccine, since IL-23 and IL-17 axis and activation of JAK-STAT is essential for immunity against Chronic Mucocutaneous Candidiasis (CMCC) and CMCC also is Mendelian disease that leishmaniasis is one of its Complications.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study reported similar observations with L. major infection and implicated both IL-4R signaling and IL-10 to contribute to susceptibility, and found that BALB/c mice deficient in both IL-4R␣ and IL-10 are more resistant to L. major infection, regardless of parasite substrain. However, in relative terms, IL-10 appears to exert a more profound effect on L. major parasite growth and the development of disease (33).…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of endogenous IL-4 results in a robust Th1 response in susceptible BALB/c mice [10,14,15]. MyD88 À/À C57BL/6 mice treated with anti-IL-4 mAb prior to infection with L. major IR75 rendered these mice resistant, whereas neutralization of IL-4 in MyD88 À/À C57BL/6 mice infected with L. major LV39 did not have the same effect.…”
Section: Susceptibility Of Myd88mentioning
confidence: 99%
“…Macrophages infected with IR173 and Friedlin V1 substrains required 25-500 fold lower concentration of IFN-g to achieve the same level of parasite killing as LV39 [10]. Similarly, IR75 substrain required tenfold lower concentration of IFN-g to achieve the same level of parasite killing than LV39 (Revaz-Breton, unpublished data).…”
Section: Ir75 Ifn-g Production Is Myd88 and Il-12 Independentmentioning
confidence: 99%
See 1 more Smart Citation